Modeling the Flood Risk of Diyala River in Baquba City Using HEC-RAS Program (Iraqi National Journal of Earth Science (INJES), 2026)
The research deals with hydraulic modeling processes to understand the behavior of rivers by creating a simulation system for river flow. This research aims to model the Diyala River flood wave in the city of Baqubah to determine the risk areas and their risk degrees. A scientific methodology is used based on quantitative analysis and computer programming, using flood wave data for the years 1988 and 2019. Also, the Hec-Ras program is used to enter engineering data, using the Manning coefficient and adding hydrological data, thereafter, and analyzing the results, drawing a risk map, and classifying it in the region. 36 cross-sections of the river course are studied, and the results at different rainfall return periods (10, 20, 50, 100 years) are utilized to predict the depth and speed of water from (7.1 m) in (10 years) to (7.5 m) in (100 years). The speed of water ranges between (0.91 m/s) in (10 years) to (1.5 m/s) in (100 years). The results of the areas that represent a varying risk to all residents in the study area indicated a percentage to (22%) of the total area of the area, which is not a small percentage compared to the size of the risk that threatens the lives and property of residents, and the necessity of state intervention to protect the lives and property of people by re-planning residential areas and treating residential areas that have encroached on the river area legally and humanely.
Keywords: Diyala, Baquba, Flood, Modeling, Wave